Psychometric properties of the Posttraumatic Cognitions Inventory (PTCI) in a German sample of individuals with a history of trauma - Müller, Julia; Wessa, Michèle; Rabe, Sirko; Dörfel, Denise; Knaevelsrud, Christine; Flor, Herta; Maercker, Andreas; Karl, Anke (Psychological trauma, 2010)
In this study, we examined the psychometric properties of the 33-item Posttraumatic Cognitions Inventory (Foa, Ehlers, Clark, Tolin, & Orsillo, 1999) in 213 individuals with accident-related trauma and 190 individuals with interpersonal trauma. Confirmatory factor analyses generally supported the scale's original three-factor structure—Negative Cognitions About Self (SELF), Negative Cognitions About World (WORLD), and Self-Blame (BLAME)—after four redundant items were excluded. However, in line with previous findings, results for BLAME remained inconclusive because the scale performed poorly with the individuals with accident-related trauma, whereas its fit with those with interpersonal trauma was acceptable. BLAME might possibly relate to trauma type. Our results indicate that the proposed 29-item version shows acceptable psychometric properties and that the role of BLAME should be further investigated. (PsycInfo Database Record (c) 2022 APA, all rights reserved)